Amyloid precursor‐like protein 1 (APLP1) exhibits stronger zinc‐dependent neuronal adhesion than amyloid precursor protein and APLP2. Issue 2 (7th March 2016) - Mayer, Magnus C.; Schauenburg, Linda; Thompson‐Steckel, Greta; Dunsing, Valentin; Kaden, Daniela; Voigt, Philipp; Schaefer, Michael; Chiantia, Salvatore; Kennedy, Timothy E.; Multhaup, Gerhard
Abstract: The amyloid precursor protein (APP) and its paralogs, amyloid precursor‐like protein 1 (APLP1) and APLP2, are metalloproteins with a putative role both in synaptogenesis and in maintaining synapse structure. Here, we studied the effect of zinc on membrane localization, adhesion, and secretase cleavage of APP, APLP1, and APLP2 in cell culture and rat neurons. For this, we employed live‐cell microscopy techniques, a microcontact printing adhesion assay and ELISA for protein detection in cell culture supernatants. We report that zinc induces the multimerization of proteins of the amyloid precursor protein family and enriches them at cellular adhesion sites. Thus, zinc facilitates the formation of de novo APP and APLP1 containing adhesion complexes, whereas it does not have such influence on APLP2. Furthermore, zinc‐binding prevented cleavage of APP and APLPs by extracellular secretases. In conclusion, the complexation of zinc modulates neuronal functions of APP and APLPs by (i) regulating formation of adhesion complexes, most prominently for APLP1, and (ii) by reducing the concentrations of neurotrophic soluble APP/APLP ectodomains. Earlier studies suggest a function of the amyloid precursor protein (APP) family proteins in neuronal adhesion. We report here that adhesive function of these proteins is tightly regulated by zinc, most prominently for amyloid precursor‐like protein 1 (APLP1). Zinc‐mediated APLP1 multimerization, which induced formation of new neuronal contacts and decreased APLP1 shedding. This suggests that APLP1 could function as a zinc receptor processing zinc signals to stabilized or new neuronal contacts. Abstract : Earlier studies suggest a function of the amyloid precursor protein (APP) family proteins in neuronal adhesion. We report here that adhesive function of these proteins is tightly regulated by zinc, most prominently for amyloid precursor‐like protein 1 (APLP1). Zinc‐mediated APLP1 multimerization, which induced formation of new neuronal contacts and decreased APLP1 shedding. This suggests that APLP1 could function as a zinc receptor processing zinc signals to stabilized or new neuronal contacts.